Studies of Acoustical Properties of Methyl Salicylate in Different Solvents - Baluja, Shipra (Asian Journal of Chemistry, 2010)
Acoustical properties in different compositions of methyl salicylate- dioxane (MS-DO), methyl salicylate-methanol (MS-MeOH) and methyl salicylate-benzene (MS-BN) were studied at 30°C using a single crystal multifrequency interferometer operating at 3 MHz. Various acoustical and thermodynamic parameters like isentropIc compressibility (Ks), specific impedance (Z), intermolecular free path (Lf), molar sound velocity (R), relaxation strength (r), the van der Waals constant (b), internal pressure (π), relaxation time (τ), classical adsorption coefficient ((α/f2)Cl), molecular diameter (dM), surface tension (σ), excess volume (VE), excess viscosity (ηE), excess sound velocity (UE), excess Gibbs free energy of activation of flow (ΔGE) etc. were evaluated using experimental data of sound velocity (U), density (ρ) and viscosity (η) at 30°C. The results are interpreted in terms of interactions taking place in solutions.